Social sustainability in the forest - Wollenberg, Eva Karoline; Colfer, C.J.P. (1996)
This article is a brief progress report of a project aiming to test criteria and indicators for the social dimensions of sustainable forest management. It explains our conceptual starting point for our research, including a defintion of well-being, our perspective on the actions of people, and brief mention of intergenerational distribution. We then provide an account of what exactly has been done in the field tests, followed by a section on lessons learned. We conclude with some ideas for next steps, and with a summary of principles, criteria, indicators and verifiers pertaining to people’s roles in sustainable forest management.